Communication for development and social transcendence: a systematic analysis focusing on social processes - Quispe-Borda, Wenceslao (2024)
Communication for development (CfD) is a discipline that seeks to promote social change through the strategic use of media and participatory dialogue. However, there is a paucity of studies that systematically and critically analyze the social processes underlying CfD interventions and their impact on the social significance of beneficiary communities. This article presents a narrative review of the literature on CfD, with the aim of identifying the main theoretical and methodological approaches that have addressed this topic, as well as the main limitations and challenges facing research in this field. Thirty-five articles published between 2018 and 2023 were analyzed, selected through a search in the Scopus, Web of Science, SciELO, Redalyc and Latindex databases. The results show that most of the studies adopt a qualitative and participatory perspective, focused on the analysis of specific cases of CfD in different geographical and thematic contexts. Four key dimensions for understanding the social processes involved in CfD are identified: participation, empowerment, dialogue and collective action. Finally, we discuss the theoretical and practical implications of these findings and propose some recommendations for future research.